Identification of a functional enhancer variant within the chronic pancreatitis‐associated SPINK1 c.101A>G (p.Asn34Ser)‐containing haplotype. Issue 8 (15th June 2017) - Boulling, Arnaud; Masson, Emmanuelle; Zou, Wen‐Bin; Paliwal, Sumit; Wu, Hao; Issarapu, Prachand; Bhaskar, Seema; Génin, Emmanuelle; Cooper, David N.; Li, Zhao‐Shen; Chandak, Giriraj R; Liao, Zhuan; et al.
Abstract : The haplotype harboring the SPINK1 101A>G variant represents the most important heritable risk factor for idiopathic chronic pancreatitis identified to date. The causal variant contained within this risk haplotype has however remained stubbornly elusive. Herein we set out to resolve this enigma by employing a hypothesis‐driven approach. We suggest that rs142703147:C>A, which disrupts a PTF1L binding site within an evolutionarily conserved HNF1A‐PTF1L cis‐regulatory module located ∼4 kb upstream of the SPINK1 promoter, contributes to the aforementioned chronic pancreatitis risk haplotype. Abstract: The haplotype harboring the SPINK1 c.101A>G (p.Asn34Ser) variant (also known as rs17107315:T>C) represents the most important heritable risk factor for idiopathic chronic pancreatitis identified to date. The causal variant contained within this risk haplotype has however remained stubbornly elusive. Herein, we set out to resolve this enigma by employing a hypothesis‐driven approach. First, we searched for variants in strong linkage disequilibrium (LD) with rs17107315:T>C using HaploReg v4.1. Second, we identified two candidate SNPs by visual inspection of sequences spanning all 25 SNPs found to be in LD with rs17107315:T>C, guided by prior knowledge of pancreas‐specific transcription factors and their cognate binding sites. Third, employing a novel cis‐regulatory module (CRM)‐guided approach to further filter the two candidate SNPs yielded a solitary candidate causal variant. Finally, combining data from phylogenetic conservation and chromatin accessibility, cotransfection transactivation experiments, and population genetic studies, we suggest that rs142703147:C>A, which disrupts a PTF1L‐binding site within an evolutionarily conserved HNF1A−PTF1L CRM located ∼4 kb upstream of the SPINK1 promoter, contributes to the aforementioned chronic pancreatitis risk haplotype. Further studies are required not only to improve the characterization of this functional SNP but also to identify other functional components that might contribute to this high‐risk haplotype.